Clinicopathological Features of Dengue Fever–a Single Center Study - Batool, Aliya (International Journal of Pathology, 2020)
Background: Dengue viral infection is an important and rapidly spreading mosquito borne infection of humans worldwide.Objective: To evaluate the clinicopathological features of patients with dengue fever.Methodology: A descriptive cross sectional study was conducted to evaluate the clinicopathological features of patients with dengue viral infection in Pakistan Atomic Energy Commission General Hospital, Islamabad. A total of 62 patients of Dengue infection were followed and documented in this study. A detailed clinical history, physical examination, and investigations were noted using a structured Performa. Tests included complete blood count (CBC), serum Aminotransferases including Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), and dengue serology.Results: Out of 62 patients with diagnosis of Dengue viral infection through Dengue serology test, 59 cases fulfilled the WHO diagnostic criteria of probable Dengue fever and 3 cases fulfilled the diagnostic criteria of Dengue Hemorrhagic Fever (DHF), including Dengue Shock Syndrome (DSS). Male to female ratio was 5׃1 and median age of the patients was 34 years (ranged from 4 to 70 years). Fever was the main symptom (100% of cases), followed by generalized body aches and pains (in 73% of cases), at the time of presentation. Mean hemoglobin level was 14 ± 1.8 gm/dl, while total leukocyte count (TLC) was <4000/µl in 84%, and platelets were <150,000/µl in 100% of the cases. Serum aminotransferases (AST, ALT) were deranged in 70% of the cases. Conclusion: This study shows slight difference in clinicopathological features of patients with dengue infection compared to those in other parts of the world, which can help the clinicians in early detection of dengue infection and on those basis further workup and management can be planned.